2015
DOI: 10.18387/polibotanica.55.7
|View full text |Cite
|
Sign up to set email alerts
|

Actividad antioxidante y citotóxica del aceite esencial de las hojas de laurel aromático (Litsea glaucescens Kunth)

Abstract: Las opiniones expresadas por los autores no necesariamente reflejan la postura del editor de la publicación.Queda estrictamente prohibida la reproducción total o parcial de los contenidos e imágenes de la publicación sin previa autorización del Instituto Politécnico Nacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…Similarly, a recent study focused on the chemical and biological activity of L. glaucescens essential oil, revealed comparable levels of eucalyptol than those reported in the present study [19] . These investigations suggested the potential use of this volatile fraction as a source of bioactive antioxidants to treat depression and some types of cancer [18–19] . The results of the antifungal tests demonstrated that LgEO produced a MIC of 1.5 mg mL −1 for both fungal species.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, a recent study focused on the chemical and biological activity of L. glaucescens essential oil, revealed comparable levels of eucalyptol than those reported in the present study [19] . These investigations suggested the potential use of this volatile fraction as a source of bioactive antioxidants to treat depression and some types of cancer [18–19] . The results of the antifungal tests demonstrated that LgEO produced a MIC of 1.5 mg mL −1 for both fungal species.…”
Section: Resultssupporting
confidence: 83%
“…The essential oil showed a similar chemical composition to that found in Litsea glaucescens grown in Veracruz México but, eucalyptol and o‐cymene were the most abundant compounds in this fraction [18] . Similarly, a recent study focused on the chemical and biological activity of L. glaucescens essential oil, revealed comparable levels of eucalyptol than those reported in the present study [19] . These investigations suggested the potential use of this volatile fraction as a source of bioactive antioxidants to treat depression and some types of cancer [18–19] .…”
Section: Resultssupporting
confidence: 83%